2016
DOI: 10.1007/s00270-016-1350-1
|View full text |Cite
|
Sign up to set email alerts
|

Ga-68 DOTATOC PET/CT-Guided Biopsy and Cryoablation with Autoradiography of Biopsy Specimen for Treatment of Tumor-Induced Osteomalacia

Abstract: Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome caused by small benign tumors of mesenchymal origin also known as phosphaturic mesenchymal tumors mixed connective tissue variant. Excellent prognosis is expected with eradication of the culprit tumor. These small tumors are notoriously difficult to localize with conventional radiographic studies; this often leads to an extensive work up and prolonged morbidity. We report a patient with clinical diagnosis of TIO whose culprit tumor was localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Other studies [2629] have shown FDG PET/CT useful for bone and soft-tissue biopsy. Werner et al [26] reported a case of FDG PET/CT–guided biopsy of bone metastases.…”
Section: Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies [2629] have shown FDG PET/CT useful for bone and soft-tissue biopsy. Werner et al [26] reported a case of FDG PET/CT–guided biopsy of bone metastases.…”
Section: Bonementioning
confidence: 99%
“…Maybody et al [29] reported results on a patient with a clinical diagnosis of tumor-induced osteomalacia in whom the culprit tumor was localized with 68 Ga-tetraazacy-clododecanetetraacetic acid–Phe1-Tyr3-octreotide PET/CT and MRI, and the biopsy was performed under PET/CT guidance. Guo et al [30] evaluated the safety and efficacy of FDG PET/CT for guiding biopsy of bone metastases in patients with advanced lung cancer.…”
Section: Bonementioning
confidence: 99%
“…In this case, a combination of ethanol injection and cryoablation was used with successful biochemical resolution and marked clinical improvement with 12 months of follow‐up. For unstated reasons, Maybody and colleagues chose image‐guided biopsy and cryoablation over surgery of a TIO tumor that was peripherally located in lateral segment of the sixth rib. At 6‐week follow‐up, there was no evidence of recurrence or tumor seeding from the biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, performing a PET scan on the biopsied tissue will be able to prove the fixation of the radiotracer in the specimen, leading to assertion of the success of the technique. 7 This success assessment can also be performed following PET/CT procedures, which, however, could me more challenging than assessing the success of biopsies. 4…”
Section: Advantages Of Pet/ct Guided Proce-duresmentioning
confidence: 99%
“…It is estimated that the PET/CT imaging required to guide a biopsy will put the patient under exposure of a radiation dose of 370 MBq. 7 Moreover, some other PET/CT guided procedures may carry a risk of higher exposures like performing multiple ablations simultaneously. 8 Unfortunately, these high doses of radiation cannot be reduced.…”
Section: Disadvantages Of Pet/ct Guided Proce-duresmentioning
confidence: 99%